The Implementation of MBKM Policy and Its Impact on the Curriculum and Learning Model - Hartono, Heny; Retnawati, Berta Bekti; Leong, Hironimus; Mulyani, Tri Hesti; Hernawati, Lucia (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
This article is a report of a research on the implementation of Merdeka Belajar Kampus Merdeka (MBKM) at Soegijapranata Catholic University  (SCU), Semarang supported by the Directorate General of Research and Technology, Directorate General of Higher Education, Republic Indonesia). This study involved 5275 respondents as the sample taken from a total of 7775 population which consisted of lecturers, administrative staff, and students. It aimed to see the implementation of MBKM at SCU and how the stakeholders perceived the impacts of MBKM implementation on the curriculum, syllabus, and learning model. This study applied sequential method by which the results of qualitative and quantitative data analysis were elaborated. The instruments used were Focus Group Discussion and SPADA survey. The results of this study showed that respondents had positive perceptions on the implementation of MBKM but not all respondents fully understood the system, process, and procedure of the MBKM implementation. The implementation of MBKM also affected the curriculum and learning model. Therefore, a model of curriculum and learning model based on contextual learning was suggested to support the implementation of MBKM at SCU.